The Monks of the Nag Hammadi Codices: Contextualising a Fourth-Century Monastic Community - Tutty, Paula (Nag Hammadi and Manichaean Studies, 2024)
This book explores the life and times of one of the earliest monastic communities and its connection to a set of extraordinary theological works now known as the Nag Hammadi Codices.